Insect Feeding Deterrents in Endophyte-Infected Tall Fescue - Johnson, M. C. (1985)
The presence of an endophytic fungus, Acremonium coenophialum, in tall fescue (Festuca arundinacea) deterred aphid feeding by Rhopalosiphum padi and Schizaphis graminum. Both species of aphid were unable to survive when confined to endophyte-infected tall fescue plants. Feeding deterrents and toxic factors to R. padi and Oncopeltus fasciatus, large milkweed bug, were primarily associated with a methanol extract obtained when endophyte-infected tall fescue seed was serially extracted with hexane, ethyl acetate, and methanol. The concentrations of pyrrolizidine alkaloids were determined to be 30 to 100 times greater in the methanol extract than in the hexane and ethyl acetate extracts.